Practical Experiments to Evaluate Quality Metrics of MRAM-Based Physical Unclonable Functions - Arash Nejat; Frederic Ouattara; Mohammad Mohammadinodoushan; Bertrand Cambou; Ken Mackay; Lionel Torres (IEEE Access, 2020)
Process variations in the manufacturing of digital circuits can be leveraged to design Physical Unclonable Functions (PUFs) that are extensively employed in hardware-based security. Different PUFs based on Magnetic Random-Access-Memory (MRAM) devices have been studied and proposed in the literature. However, most of these studies have been simulation-based, which do not fully capture the physical reality. We present experimental results on a PUF implemented on dies fabricated with a type of the MRAM technology namely Thermally-Assisted-Switching MRAM (TAS-MRAM). To the best of our knowledge, this is the first experimental validation of a TAS-MRAM-based PUF. We demonstrate how voltage values used for writing in the TAS-MRAM cells can make stochastic behaviors required for PUF design. The analysis of the obtained results provides some preliminary findings on the practical application of TAS-MRAM-based PUFs in authentication protocols. Besides, the results show that for key-generation protocols, one of the standard error correction methods should be employed if the proposed PUF is used.